Proceedings of the Tenth Conference on European Chapter of the Association for Computational Linguistics - EACL '03 2003
DOI: 10.3115/1067737.1067740
|View full text |Cite
|
Sign up to set email alerts
|

Clustering adjectives for class acquisition

Abstract: This paper presents an exploratory data analysis in lexical acquisition for adjective classes using clustering techniques. From a theoretical point of view, this approach provides large-scale empirical evidence for a sound classification. From a computational point of view, it helps develop a reliable automatic subclassification method.Results show that the features used in theoretical work can be successfully modelled in terms of shallow cues. The resulting clusters parallel to a large extent with proposals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the future, the models need to be extended to identify not only verb-subject and verb-object metaphors, but also metaphorical expressions in other syntactic constructions (e.g., adjectival or nominal metaphors). Previous distributional clustering and lexical acquisition research has shown that it is possible to model the meanings of a range of word classes using similar techniques (Hatzivassiloglou and McKeown 1993;Boleda Torrent and Alonso i Alemany 2003;Brockmann and Lapata 2003;Zapirain, Agirre, and Màrquez 2009). We thus expect our methods to be equally applicable to metaphorical uses of other word classes and syntactic constructions.…”
Section: Discussionmentioning
confidence: 89%
“…In the future, the models need to be extended to identify not only verb-subject and verb-object metaphors, but also metaphorical expressions in other syntactic constructions (e.g., adjectival or nominal metaphors). Previous distributional clustering and lexical acquisition research has shown that it is possible to model the meanings of a range of word classes using similar techniques (Hatzivassiloglou and McKeown 1993;Boleda Torrent and Alonso i Alemany 2003;Brockmann and Lapata 2003;Zapirain, Agirre, and Màrquez 2009). We thus expect our methods to be equally applicable to metaphorical uses of other word classes and syntactic constructions.…”
Section: Discussionmentioning
confidence: 89%
“…One important task in lexical acquisition is the extraction of verb frames and subcategorization frames from corpora (see, e.g., [21]). There has also been a lot of work on clustering adjectives by their semantics [3,6]. Further work has addressed the extraction of hyponyms and hypernyms from corpora [14], and of identifying the particular meaning of adjectives in adjective-noun phrase compounds, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…1999, associative adjectives (Ferris 1993, Giegerich 2005, relational adjectives (Fellbaum κ.ά. 1993, McNally & Boleda 2004, Boleda Torrent & Alonso i Alemany 2003, denominal adjectives (Coates 1971, Quirk κ.ά. 1972, denominal (relative) adjectives (Raskin & Nirenburg 1998),…”
Section: κριτήρια κατηγοριοποίησηςmentioning
confidence: 99%